Persuasive Dawah Strategies for Inmates on State Detention Centers in East Java - Salikin, Hairus; Wahyuningsih, Indah; Wahyuningsih, Agung Tri (KARSA Journal of Social and Islamic Culture, 2021)
This article is the results of the study conducted in three detention centers in Jember, Bondowoso, and Situbondo. The focus of the study is how preachers use some techniques of rhetoric to persuade the assisted residents to fear Allah. This is of importance looking at the fact that assisted residents need religious messages while they are in the detention centers. The data of the study was collected by recording the religious talks delivered by the preachers and conducting the observation. The spoken data was transcribed into written, spoken texts. The preachers’ utterances were sorted out to find the utterances containing persuasive elements. Then they were analyzed as the basis of identifying the techniques which were used by the preachers to persuade the assisted residents. The results of the study reported that there was persuasive rhetoric in religious talks at those three detention centers. That persuasive rhetoric was applied using different techniques: direct and indirect persuasion, figurative language, references, story, and the use of cause and effect techniques.